New traveling wave solutions of the higher dimensional nonlinear evolution equation by the improved (G′/G) expansion method - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali (© 2012 World Applied Sciences Journal, 2016)
This article was published in World Applied Sciences Journal [©2012 IDOSI Publications.]